Course and Program Outcomes Assessment Methods in Outcome-Based Education: A Review. Issue 3 (October 2019) - Premalatha, K.
In Outcome-Based Education (OBE), the assessment of the Course Outcomes (COs) is the most prominent aspect required to improve the quality of education. The COs for each course are based on the Program Outcomes (POs), Program Specific Outcomes (PSOs), and other requirements. There are various understandings toward the concept of OBE that resulted in various attainment to PO based on the CO. This article describes the framework of OBE and detailed survey on CO-PO mapping and its attainment models. This article serves as guidelines of writing COs, and mapping CO and PO and its attainment.